Characterization of the coffee fruit detachment force in crop subjected to mechanized harvesting - Ferreira Júnior, Luiz de Gonzaga; Silva, Fábio Moreira da; Ferreira, Danton Diego; Simão, Sérgio Domingos; Souza, Gabrielly Carvalho de; Ferreira, Lucas Kemps (Coffee Science - ISSN 1984-3909, 2018)
In order to adjust the coffee harvester and to assist in deciding either whether or not to make a second pass of the harvester, fully or selectively, it is necessary to know some crop parameters. The aim of the present study was to evaluate the coffee fruit detachment force in the green and cherry ripeness, under different plant positions and in four evaluation periods, throughout the harvest period between the first and second pass of harvester. The cultivar used was the Catuaí Amarelo IAC 144 aged eight years in spacing 3.8 x 0.9 m. Detachment force was determined by sampling using a portable digital dynamometer. The green ripeness stage showed superior detachment force than the cherry for all evaluation periods. The fruit detachment force for the green and cherry ripeness showed a decreasing behavior during the evaluation period, since the difference between the detachment forces of these fruits increased, thus guiding the type of harvest to be performed. Beyond the fruit detachment force difference, other parameters such as fruit ripening rate and crop load were essential for harvest management. Significant variations were identified in the fruit detachment force positioned in different parts of the coffee tree branches. The results also reinforce the relevance of characterizing the coffee fruit detachment force for harvester adjustments and management of the selective mechanized harvesting.